Role of the very low frequencies of the renal oxygen saturation signal in acute kidney injury in newborns with perinatal asphyxia - Daniel Botero-Rosas; Sergio Agudelo-Pérez; Sergio Agudelo-Pérez; Gloria Troncoso; Maria C. Gómez; Eduardo Tuta-Quintero (Frontiers in Pediatrics)
ObjectiveRenal autoregulation, hemodynamic response, and endothelial dysfunction play significant roles in acute kidney injury (AKI) during perinatal asphyxia. A third mechanism of autoregulation, involving very low-frequency oscillations, has been described. This study aimed to evaluate the relationship between the power of the very low-frequency component of the Fast Fourier Transform (FFT) and AKI during therapeutic hypothermia (TH) treatment in neonates with perinatal asphyxia.Study designA retrospective longitudinal study was conducted on neonates with moderate and severe perinatal asphyxia. AKI was defined as a decrease of less than 33% in the serum creatinine level by day 3. The power of the very low-frequency component in the FFT was assessed by analyzing renal oxygen saturation using near-infrared spectroscopy (NIRS), focusing on a frequency band of approximately 0.01 Hz. Bivariate analyses were performed to explore the association between the power of the very-low-frequency component and AKI. The predictive ability of this component for AKI was evaluated using a receiver operating characteristic (ROC) curve. Additionally, a generalized estimating equation (GEE) was developed to investigate whether changes in the power of the very-low-frequency component during treatment differed according to the presence of AKI.ResultsA total of 91 patients were included in the study, of whom 15 (16.5%) developed AKI. Neonates with AKI exhibited a significantly lower power of the very low-frequency component on the second day of treatment (p = 0.001). This component demonstrated good predictive ability for AKI (ROC curve 0.77, 95% CI 0.63–0.90).ConclusionAmong neonates with perinatal asphyxia who developed AKI, a lower power of the very-low-frequency component in FFT (approximately 0.01 Hz) was observed on the second day of therapeutic hypothermia. This finding suggests that alterations in very-low-frequency oscillations may reflect endothelial dysfunction and contribute to the development of AKI, warranting further investigation in larger cohorts.